2015
DOI: 10.1007/s00439-015-1585-y
|View full text |Cite
|
Sign up to set email alerts
|

Whole exome sequencing in extended families with autism spectrum disorder implicates four candidate genes

Abstract: Autism spectrum disorders (ASD) are a group of neurodevelopmental disorders, characterized by impairment in communication and social interactions, and by repetitive behaviors. ASDs are highly heritable, and estimates of the number of risk loci range from hundreds to > 1000. We considered 7 extended families (size 12 – 47 individuals), each with ≥ 3 individuals affected by ASD. All individuals were genotyped with dense SNP panels. A small subset of each family was typed with whole exome sequence (WES). We used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
57
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 70 publications
(80 reference statements)
6
57
0
1
Order By: Relevance
“…present in family P1). Although we were quite liberal in selecting regions for further analysis (through including suggestive linkage signals), the observed pattern is similar to findings in previous linkage studies of ADHD [13,14] and other neurodevelopmental disorders (e.g., for ASDs [53]). …”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…present in family P1). Although we were quite liberal in selecting regions for further analysis (through including suggestive linkage signals), the observed pattern is similar to findings in previous linkage studies of ADHD [13,14] and other neurodevelopmental disorders (e.g., for ASDs [53]). …”
Section: Discussionsupporting
confidence: 82%
“…With this in mind, our combined linkage and WES approach did help to efficiently limit the list of potentially causative variants in a data-driven way. Filtering WES variants by linkage analysis has earlier been shown to be an effective tool for prioritizing common and exome variants in extended families with ADHD [14] or ASD [53].…”
Section: Discussionmentioning
confidence: 99%
“…For each proband, available family members were genotyped to determine if they carry the variant allele. Primers for PCR amplification and sequencing were designed using Primer3 (v 4.0.0) and bidirectional sequencing on an ABI 3730 DNA analyzer (Applied Biosystems) was done as previously described 13 .…”
Section: Methodsmentioning
confidence: 99%
“…To identify genes involved in familial autism, new sequencing methods were initially applied in consanguineous affected individuals in order to detect recessive genes 10, 11 . More recently whole-exome sequencing (WES) has been used in multiplex families to identify heterozygous shared variants that are associated with ASD risk 12, 13 . Such studies identified additional candidate genes for autism but lacked statistical power and did not include replication 14 .…”
Section: Introductionmentioning
confidence: 99%
“…In this context, next‐generation sequencing (NGS) technology, by evaluating rare genetic variants, has enabled a deeper examination of complex traits using alternate models of risk, such as the ‘oligogenic quasi‐Mendelian model’ and the ‘omnigenic models’ of inheritance. Several recent studies in autism, SCZ, BD, and depression have detected rare variants using NGS in case–control or family‐based designs, across different genes implicated to play a key role in critical biological pathways . Findings from such studies have shown that the majority of the rare variants identified are private to a family (Table S1), indicating the underlying heterogeneity in the genetic architecture of SMI.…”
mentioning
confidence: 99%